Inferring the concentration of dark matter subhaloes perturbing strongly lensed images. Issue 1 (31st July 2021) - Minor, Quinn; Kaplinghat, Manoj; Chan, Tony H; Simon, Emily
ABSTRACT: We demonstrate that the perturbations of strongly lensed images by low-mass dark matter subhaloes are significantly impacted by the concentration of the perturbing subhalo. For subhalo concentrations expected in Lambda cold dark matter (ΛCDM), significant constraints on the concentration can be obtained at Hubble Space Telescope ( HST ) resolution for subhaloes with masses larger than about $10^{10}\, {\rm M}_\odot$ . Constraints are also possible for lower mass subhaloes, if their concentrations are higher than the expected scatter in CDM. We also find that the concentration of lower mass perturbers down to $\sim 10^8\, {\rm M}_\odot$ can be well constrained with a resolution of ∼0.01 arcsec, which is achievable with long-baseline interferometry. Subhalo concentration also plays a critical role in the detectability of a perturbation, such that only high-concentration perturbers with mass $\lesssim 10^9\, {\rm M}_\odot$ are likely to be detected at HST resolution. If scatter in the ΛCDM mass–concentration relation is not accounted for during lens modelling, the inferred subhalo mass can be biased by up to a factor of 3 (6) for subhaloes of mass $10^9 \, {\rm M}_\odot \, (10^{10} \, {\rm M}_\odot$ ); this bias can be eliminated if one varies both mass and concentration during lens fitting. Alternatively, one may robustly infer the projected mass within the subhalo's perturbation radius, defined by its distance to the critical curve of the lens being perturbed. With a sufficient number of detections, these strategies will make it possible to constrain the halo mass–concentration relation at low masses in addition to the mass function, offering a probe of dark matter physics as well as the small-scale primordial power spectrum.